Enhanced Drug Permeation into Human Keloid Tissues by Sonophoresis-Assisted Microneedling. (December 2021) - Yang, Yating; Xia, Lingling; Ning, Xiaoyu; Hu, Tianli; Xu, Chenjie; Liu, Wei
Keloids are disfiguring pathological scars that could cause pain and pruritus. The conventional treatments, such as bolus injection of drugs or surgery, are invasive and require a personal visit to clinic. Microneedle (MN) technology has great potential to offer a self-administered and minimally invasive treatment of keloids. However, drugs delivered using MNs suffer from limited penetration in keloid tissue. This study demonstrates enhanced drug penetration in human keloid scar tissue by combining MN and sonophoresis.